The Attitude Of The Midwife Towards The Implementation Of Early Initiation Of Breastfeeding With Exclusive Breastfeeding At Kuala Health Center, Kuala Subdistrict, Langkat Regency In 2021 - Faradita Wahyuni; Nurhamida Fithri; Selli M Pasaribu (International Journal of Cultural and Social Science, 2021)
Objectives: Midwives as health workers who assist in childbirth are a very important factor in the practice of IMD and most midwives do not implement it. This will affect the implementation of the Exclusive Breastfeeding program. The purpose of this study was to determine the relationship between midwives' attitudes regarding the implementation of early initiation of breastfeeding with low coverage of exclusive breastfeeding. Method: The method used was an analytical survey (Explanatory Research) with a cross sectional approach. The population is all midwives who work in the Kuala District Health Center, Kuala District, Langkat Regency as many as 31 people. The sample, namely the entire population, became a total sampling with Chi-Squere analysis. Results: Based on the results of the analysis of the Relationship of Midwives' Attitudes regarding Implementation of Early Breastfeeding Initiation with Low Exclusive Breastfeeding Coverage, it was found that the negative attitude of midwives with the target not being achieved was 19 respondents (61.3%) and positive attitude as many as 12 respondents (38.7%). Based on a population of 31 respondents, the results of statistical tests obtained p value = 0.006 <0.05, so it can be concluded that there is a significant relationship between Midwives' Attitudes About IMD Implementation and Low Exclusive Breastfeeding Coverage. Conclusion: The research is that there is a relationship between midwives' attitudes about the implementation of IMD with the low coverage of exclusive breastfeeding. Midwives are expected to be able to increase a positive attitude about the implementation of IMD as an effort to increase exclusive breastfeeding.